The Existence and Uniqueness of Periodic Solutions for Some Nonlinear nth-Order Differential Equations - Qiyuan Zhou; Shuhua Gong (Abstract and Applied Analysis)
The nonlinear nth-order differential equations are considered. By using inequality techniques and coincidence degree theory, some criteria are obtained to guarantee the existence and uniqueness of T-periodic solutions for the equations. The obtained results are also valid and new for the problem discussed in the previous literature. Moreover, two illustrative examples are provided to illustrate the effectiveness of our results.